Effect of environment temperature on web tension in shaft-less drive gravure printing system. (February 2019) - He, Kui; Liu, Shanhui; Wang, Kedian; Mei, Xuesong
In the printing section of the shaft-less drive gravure printing machine, as the web material is sensitive to temperature, the web outside the drying devices will be affected by the changes of the environment temperature. In order to improve the printing precision in gravure printing machine, the effects of environment temperature on web tension in the printing section are studied in this article. Based on the law of mass conservation, the tension model including the factor of environment temperature is derived. Then some theoretical analyses and simulations are conducted to in-depth study the effects of environment temperature from the relations between inputs and output in a web span. Finally, some experiments are carried out to verify the characteristics of the tension subsystem including environment temperature. The result shows that the settling times decrease with the rise of the environment temperature in the transient responses, and the absolute changes of the steady-state tension decrease with the rise of the environment temperature in the steady-state responses as the inputs are the velocities of the printing rollers. The study on the effects of environment temperature on web tension would benefit the tension control and the register control for the further study.